The Communication Culture of the Cyberspace in the Perspective of Language Politeness - Haerul Haerul; Andoyo Sastramiharjo; Vismaia S. Damaianti; Yeti Mulyati (Ethical Lingua: Journal of Language Teaching and Literature, 2021)
Cross cultural communication based on cyberspace is one part of the globalization era. The virtual world becomes a multicultural communication space that forms a new culture. This research was conducted to analyze the politeness of language in cyberspace. Conversations from 10 Twitter accounts of politicians were used as a source of data for this study and analyzed using Leech politeness maxim theory. This research was conducted using qualitative descriptive methods. The results of this study indicate that the violations of politeness maxim that often occur are violations of the maxim of wisdom, the maxim of generosity, the maxim of appreciation, and maxim of simplicity. Violations of politeness in language are manifested in the form of hoaxes and hate speech. This happens because when people communicate in cyberspace, they embrace a new communication culture that lacks ethical considerations and tastes. The Communication Culture of the Cyberspace in the Perspective of Language Politeness. Based on the results of this study, it can be concluded that a new communication culture has been created on social media. Communication culture is a blend of various cultures in Indonesia, even in the world. The integration of communication cultures occurs as a result of globalization. There has been a shift in the culture of communication, especially in the perspective of politeness in language.